Relaksasi Benson Terhadap Kecemasan Pasien Lansia Dengan Katarak Di RSUD dr. H. Jusuf SK - Maryam Sribayani; Donny Tri Wahyudi; Sulidah Sulidah; Ana Damayanti; Darni Darni (NAJ Nursing Applied Journal, 2024)
Cataract patients may experience anxiety due to a decrease in the sense of vision of the eye. coupled with surgery to overcome cataracts can increase anxiety in patients. Relaxation is an alternative to reducing anxiety. Relaxation is often used to describe a pleasant exercise with relaxation techniques used. One of the relaxations that can be used is Benson relaxation, which is a relaxation approach that involves patient trust. This study aims to analyze the benson relaxation of elderly patients with cataracts at RSUD dr. H Jusuf SK. The research method is quasi-experiment design one group pretest-posttest with a total research sample of 20 respondents. The results of the Wilcoxon test with p <0.005 that there is a difference in the anxiety level of elderly patients with cataracts at RSUD dr H Jusuf SK with p <0.05. The conclusion of the study is that there is a difference in giving Benson relaxation to the anxiety of elderly patients with cataracts.